PENGARUH KEPERCAYAAN MEREK, EKUITAS MEREK, DAN HARGA TERHADAP LOYALITAS KONSUMEN PADA PASTA GIGI MEREK PEPSODENT DI KOTA PADANG - Selvi Yona Tamara; Tri Andi Eka Putra (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2021)
To compete with Pepsodent, several toothpaste manufacturers have adopted different strategies. One way is to use attractive packaging, low price, and quality. This study aims to investigate brand trust, brand equity, and price on consumer loyalty. The sampling technique used in this study was purposive sampling where the number of samples used was 138 people. Research respondents prove that brand trust has a positive and significant effect on loyalty. Brand equity has a positive and significant effect on loyalty. Price has a positive and significant effect on loyalty.